MODOMICS: a database of RNA modification pathways. 2017 update. Issue Volume 46:Issue D1(2018) (2nd November 2017) - Boccaletto, Pietro; Machnicka, Magdalena A; Purta, Elzbieta; Piątkowski, Paweł; Bagiński, Błażej; Wirecki, Tomasz K; de Crécy-Lagard, Valérie; Ross, Robert; Limbach, Patrick A; Kotter, Annika; Helm, Mark; Bujnicki, Janusz M
Abstract: MODOMICS is a database of RNA modifications that provides comprehensive information concerning the chemical structures of modified ribonucleosides, their biosynthetic pathways, the location of modified residues in RNA sequences, and RNA-modifying enzymes. In the current database version, we included the following new features and data: extended mass spectrometry and liquid chromatography data for modified nucleosides; links between human tRNA sequences and MINTbase - a framework for the interactive exploration of mitochondrial and nuclear tRNA fragments; new, machine-friendly system of unified abbreviations for modified nucleoside names; sets of modified tRNA sequences for two bacterial species, updated collection of mammalian tRNA modifications, 19 newly identified modified ribonucleosides and 66 functionally characterized proteins involved in RNA modification. Data from MODOMICS have been linked to the RNAcentral database of RNA sequences. MODOMICS is available at http://modomics.genesilico.pl .